Bargaining failure and freedom to operate: Re-evaluating the effect of patents on cumulative innovation - Fabian Gaessler; Dietmar Harhoff; Stefan Sorg (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
We investigate the causal effect of patent rights on cumulative innovation, using large-scale data that approximate the patent universe in its technological and economic variety. We introduce a novel instrumental variable for patent invalidation that exploits personnel scarcity in post-grant opposition at the European Patent Office. We find that patent invalidation leads to a highly significant and sizeable increase of follow-on inventions. The effect is driven by cases where the removal of the individual exclusion right creates substantial freedom to operate for third parties. Importantly, our results suggest that bargaining failure between original and follow-on innovators is not limited to environments commonly associated with high transaction costs.
Keywords: K41; L24; O31; O32; O33; O34; 330; cumulative innovation; patents; bargaining failure; freedom to operate; opposition